Pengaruh Indeks Massa Tubuh terhadap Kejadian Mual Muntah Post Operasi - Marta Tania Gabriel Ching Cing; Tati Hardiyani (Universitas Faletehan, 2022)
Calculation of Body Mass Index (BMI) needs to be known before surgery in order to minimize the cause of nausea and vomiting after surgery due to side effects of anesthesia. Post-Operative Nausea and Vomiting (PONV) can cause medical complications, psychological effects, and hamper the overall therapy process so that it reduces the recovery rate of postoperative patients and affects the burden of care costs during treatment. The research purpose was to examine the correlation between Body Mass Index and the incidence of post-operative nausea and vomiting. The research used cross-sectional method. The samples were 30 postoperative respondents with inclusion and exclusion criteria. The data collection used the questionnaire of nausea and vomiting from Rhodes Index Nausea, Vomiting and Retching (Rhodes INVR). The results of univariate analysis showed as many as 56.7% of respondents experienced mild PONV and 73.3% of respondents had normal range of BMI. The bivariate analysis used an unpaired comparative test more than two groups. The test results obtained p value 0.201 > 0.05; thus, there is no significant effects of Body Mass Index on the incidence of post-operative nausea and vomiting.